2016
DOI: 10.1038/srep21955
|View full text |Cite
|
Sign up to set email alerts
|

hTERT mediates gastric cancer metastasis partially through the indirect targeting of ITGB1 by microRNA-29a

Abstract: Human telomerase reverse transcriptase (hTERT) plays a key role in tumor invasion and metastasis, but the mechanism of its involvement in these processes is not clear. The purpose of this study is to investigate the possible molecular mechanism of hTERT in the promotion of gastric cancer (GC) metastasis. We found that the up-regulation of hTERT in gastric cancer cells could inhibit the expression of miR-29a and enhance the expression of Integrin β1 (ITGB1). In addition, the invasive capacity of gastric cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 33 publications
2
48
0
Order By: Relevance
“…PXDN levels were found to be elevated in primary glial and secondary metastatic brain tumours as well as in its immediate microvasculature (Liu et al ., 2010). Similarly, ITGB1, a cell adhesive molecule, which functions to mediate association between cells and the ECM, has also been found to be misregulated in various cancers and found to impact malignant phenotypes such as invasion, proliferation and angiogenesis (He et al ., 2016; Zhang and Zou, 2015). A study also suggested the role of ITGB1 in the secretion and activation of MMP14 (Mori et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…PXDN levels were found to be elevated in primary glial and secondary metastatic brain tumours as well as in its immediate microvasculature (Liu et al ., 2010). Similarly, ITGB1, a cell adhesive molecule, which functions to mediate association between cells and the ECM, has also been found to be misregulated in various cancers and found to impact malignant phenotypes such as invasion, proliferation and angiogenesis (He et al ., 2016; Zhang and Zou, 2015). A study also suggested the role of ITGB1 in the secretion and activation of MMP14 (Mori et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Integrin β1 (ITGB1) is a type of cell adhesion molecule that mediates mutual adhesion between cells and Extracellular Matrix (ECM). ITGB1 is often abnormally expressed in tumors and is implicated in aberrant proliferation, angiogenesis, invasion and metastasis [3334]. Hypoxia-inducible factor 1a (HIF1a) is an essential transcription factor for cellular adaptation to hypoxia in cancer [3536].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are numerous studies establishing the role of hTERT in invasion and metastasis in several tumor types such as urological tumors [14][15][16][17][18], melanomas [16,19,20], gastric cancer [21][22][23][24], gliomas [15,[25][26][27][28], and hepatocellular tumors, but only very few investigated the mechanism behind this observed pattern or this coherence.…”
Section: Role Of Telomerase Reverse Transcriptase In Cancer Metastasismentioning
confidence: 99%